Use of Antipsychotic in Dementia Patients: A Desriptive Study - Muhammad Hilal Atthariq Ramadhan; Bintang Arroyantri Prananjaya; Ziske Maritska (Scientia Psychiatrica, 2020)
Introduction: Dementia is a chronic progressive syndrome in which there is a decrease in the function of cognitive abilities including memory impairment, thinking ability, orientation, understanding, calculation, language, and assessment but without impaired consciousness. Apart from cognitive impairment, dementia is often accompanied by psychological symptoms and behavioural symptoms so that antipsychotic therapy is needed to overcome this. This study aims to identify the description of the use of antipsychotics in patients with dementia at Dr Mohammad Hoesin General Hospital Palembang in the period 1 January 2014-31 December 2018. Methods: This research was a descriptive study using secondary data in the form of medical records of dementia patients receiving antipsychotic therapy at Dr Mohammad Hoesin General Hospital Palembang. Samples were taken using a total sampling method. Results: There were 29 dementia patients (38.67%) receiving antipsychotic therapy. Most of the dementia patients who received antipsychotic therapy were in the late elderly age (27.59%) and were female (55.17%). The most commonly administered antipsychotic drug is haloperidol from the dopamine receptor antagonist (60%) with the most frequent dose of 0.5 mg (34.48%). Risperidone from the serotonin-dopamine antagonist class is the second most frequently prescribed antipsychotic drug (34.28%) at a dose of 1 mg (17.28%). The mean of haloperidol was 425 days, and risperidone was 295.5 days. Conclusion: Although in theory, psychological and behavioural symptoms are often found in dementia cases, not all dementia patients in Dr Mohammad Hoesin General Hospital Palembang received antipsychotic therapy. People living with dementia who receive antipsychotic treatment get various types of drugs, dosages, and frequencies.